The Effect of Customer Review, Influencer Review, and Customer Innovativeness on Green Purchase Intention Moderated by Trust - Michella Mulyana Putri; Kuswati, Rini (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the impact of customer reviews, influencer reviews, and customer innovativeness on green purchase intention in the eco-friendly skincare market, with trust as a moderating variable. Using a quantitative approach with SmartPLS and a sample of 205 respondents familiar with eco-friendly skincare, the study confirms that all three predictors significantly enhance green purchase intention. Interestingly, trust plays a dual role directly strengthening purchase intention while weakening the influence of reviews and innovativeness when acting as a moderator. This suggests that consumers with higher trust, particularly in the brand or product, may rely more on prior experience or internal beliefs than on external cues. The study extends existing literature by emphasizing the multidimensional nature of trust and highlighting the interplay between internal and external drivers of green behavior. Despite methodological appropriateness, limitations in sample diversity and potential response bias suggest directions for future research.